Assessment of sanitation and drinking water facilities among slum households in Bhubaneswar, Odisha – A cross-sectional study - Alice Alice; Deepanjali Behera; Manas Ranjan Behera; Shantanu Kumar Patra; Jayanti Mishra (Journal of Family Medicine and Primary Care)
Aim: The study aims to assess the practice of using unsafe drinking water and sanitary practices among the population dwelling in slum settings of Bhubaneswar city, Odisha, India. Subjects and Methods: A cross-sectional study was conducted among 288 households in the Bhubaneswar slums of Chandrasekharpur, Neeladri Vihar, and Trinatha basti. A questionnaire was administered face to face. Descriptive statistics were used to define the participants’ sociodemographic characteristics, household information, drinking water, latrine characteristics, and waste disposal. Results: The majority (59.7%) resided in kutcha households in notified slum areas, and 89.6% were reportedly illiterate. About 92.7% resided in a deplorable condition, relying on piped water (79.5%) from the community sources and 20.5% used it for drinking and household purposes. Around 83% of the respondents stated they did not treat water before consumption. Bathroom facilities were found to be inadequate, and 74.3% used pit latrines. The majority of household wastes (83%) were managed by directly letting them to the drainage system untreated. As a consequence, 91% reported breeding of flies and mosquitoes near their household premises and 70.5% stated having fever in the past 6 months. Conclusion: Despite the government’s initiatives to improve water, sanitation, and hygiene (WASH) strategies, an extensive gap in practice was observed. As a result, Bhubaneswar municipality must strictly enforce policy and regulatory guidelines concerning WASH to improve the sanitation practices, particularly in the areas of drinking water and household waste management.